PENINGKATAN KECERDASAN KINESTIK ANAK MELALUI PEMBELAJARAN TARI TOPI MALANGAN PADA KELOMPOK B DI RA KALIMOSODO GEDANGAN-MALANG - Purwanti, Yuli; Sholichah, Norma Ita (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2020)
The activities of malang hat dance that require basic movement techniques as learning for early childhood. It seems that poor hat dance has difficulty level that requires agility, accuracy, and speed precisely. The purpose of the study was to describe the increase in children's kinesthetic intelligence through malangan hat dance in group B in RA Kalimosodo Gedangan-Malang. Classroom Action Research (Action Research) by applying two cycles through the process of planning, implementation, observation and reflection. Data collection techniques are done by interview, observation, and documentation. The results of the assessment and discussion carried out through Cycle I and Cycle II focused on movement techniques based on agility, accuracy, and speed with the final result of the success indicator process 64% to 84%. This study experienced an increase between cycles with a percentage of 20% with a moderate category that manifested the success in the application of the malangan hat dance activity that could improve kinesthetic intelligence in group B children.